MATHEMATICAL CONCEPTS ON BATIK BANTEN MOTIFS - Syari, Mira Hayati; Mastinah, Titin; laela, Ida; Safira, Elsa; Kusuma, Jaka Wijaya; Sulistyo, Monica Anselia Shinta (Yayasan Education and Social Center, 2022)
Ethnomathematics applies mathematical concepts associated with cultural phenomena carried out by a group of people and others. Indonesia is one of the countries that have cultural wealth from various regions. One of these cultures is batik. Batik can be associated with mathematical concepts; various regions own batik. Banten is one of the batik artisan provinces. It is time for us as a younger generation to help preserve and even introduce batik to remain famous in modern times like this. Banten has a variety of batik motifs that we will discuss such as baduy kahuripan, tambakbaya, queen girlfriend, pasepan and gula sakojor. All motives have their philosophy. Ethnomamatics research is qualitative research using ethnographic approaches. The research results obtained that in addition to containing philosophy of various motives. Motifs in batik also have continuity with mathematical concepts such as revival, cooperation, symmetry, and concepts on geometric transformations such as translation, dilation, reflection, and even rotation